(untitled) (Revista Inclusiones, 2020)
At present, the problem of finding business niches and opportunities within a specific territory, taking into account the current location of the productive forces, natural-geographic, resource, production and other potentials for the development of the region becomes urgent. In this regard, it is necessary to assess the entrepreneurial and innovative potential of specific territories, including from the perspective of favoring the development of small and medium-sized businesses. In the article the authors reveal the essence of the main methods for assessing the innovation activity of the regions: growth poles concept, methodology for drawing up the investment rating of Russian regions, investment newspaper methodology, the methodology for assessing the investment climate of the territory. The purpose of the article is to identify the innovation activity of municipal units in the Republic of Bashkortostan using the integral estimation of innovation activity. A consolidated list of indicators for assessing the management system of MUs is proposed. Comparison of MUs innovation activity indices and innovation policy made it possible to identify 4 groups of MUs. The materials of the article can be useful for local authorities.